Poorer Right Ventricular Systolic Function and Exercise Capacity in Women After Repair of Tetralogy of Fallot: A Sex Comparison of Standard Deviation Scores Based on Sex-Specific Reference Values in Healthy Control Subjects - Sarikouch, Samir; Boethig, Dietmar; Peters, Brigitte; Kropf, Siegfried; Dubowy, Karl-Otto; Lange, Peter; Kuehne, Titus; Haverich, Axel; Beerbaum, Philipp (Circulation. Cardiovascular imaging, 2013)
In repaired congenital heart disease, there is increasing evidence of sex differences in cardiac remodeling, but there is a lack of comparable data for specific congenital heart defects such as in repaired tetralogy of Fallot. In a prospective multicenter study, a cohort of 272 contemporary patients (158 men; mean age, 14.3±3.3 years [range, 8-20 years]) with repaired tetralogy of Fallot underwent cardiac magnetic resonance for ventricular function and metabolic exercise testing. All data were transformed to standard deviation scores according to the Lambda-Mu-Sigma method by relating individual values to their respective 50th percentile (standard deviation score, 0) in sex-specific healthy control subjects. No sex differences were observed in age at repair, type of repair conducted, or overall hemodynamic results. Relative to sex-specific controls, repaired tetralogy of Fallot in women had larger right ventricular end-systolic volumes (standard deviation scores: women, 4.35; men, 3.25; P=0.001), lower right ventricular ejection fraction (women, -2.83; men, -2.12; P=0.011), lower right ventricular muscle mass (women, 1.58; men 2.45; P=0.001), poorer peak oxygen uptake (women, -1.65; men, -1.14; P<0.001), higher VE/VCO2 (ventilation per unit of carbon dioxide production) slopes (women, 0.88; men 0.58; P=0.012), and reduced peak heart rate (women, -2.16; men -1.74; P=0.017). Left ventricular parameters did not differ between sexes. Relative to their respective sex-specific healthy control subjects, derived standard deviation scores in repaired tetralogy of Fallot suggest that women perform poorer than men in terms of right ventricular systolic function as tested by cardiac magnetic resonance and exercise capacity. This effect cannot be explained by selection bias. Further outcome data are required from longitudinal cohort studies.